Implementasi Nilai-Nilai Pendidikan Islam dalam Tradisi Nahu Sanamang Negeri Tulehu Kabupaten Maluku Tengah - Nahumarury, Verawati (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2026)
This research aims to determine the implementation of the nahu sanamang tradition in Tulehu Village, Salahutu District, Central Maluku Regency, the values of Islamic Education within the nahu sanamang tradition, and the implementation of these Islamic Education values in Tulehu Village, Salahutu District, Central Maluku Regency. This type of research is qualitative with a field research method using an ethnographic approach. There were 7 informants involved in this study. The data collection techniques used in this research included observation, interviews, and documentation. The data analysis techniques consisted of data reduction, data presentation, and conclusion drawing. The results of the study show that the implementation of the nahu sanamang tradition in Tulehu Village, Salahutu District, Central Maluku Regency, is carried out by the groom's side. It begins with a proposal that includes determining the amount of the dowry/wealth and the day of execution for the nahu sanamang tradition, followed by the preparation process up to the closing of the tradition. Nahu sanamang itself was established as a forum for brotherhood among all members of the Tulehu community to work together in easing the burden on the family holding the wedding. The values of Islamic education in the nahu sanamang tradition in Tulehu Village, Salahutu District, Central Maluku Regency, reflect a goodness that must be practiced as part of Creed (Aqidah) or belief values, Charity (Sedekah) values, Friendship/Kinship (Silaturahim) values, Tolerance (Toleransi) values, and Mutual Assistance (Tolong-menolong) values as a means to strengthen the bonds of brotherhood among the community in Tulehu Village. The implementation of Islamic Education values in the nahu sanamang tradition includes mutual respect among relatives, cooperation in community life, and maintaining the mandate of the village's customs and traditions that have been passed down from generation to generation in Tulehu Village. Keywords: Islamic Education Values, Nahu Sanamang Tradition.